SIMANTAP: DEGREE AUDIT MODULE AND OUTCOME-BASED EDUCATION (OBE) MODULE IMPLEMENTATION - Ariawan, Eko (Universitas Bunda Mulia, 2024)
Sistem Manajemen Tata Kelola Pendidikan Tinggi (SIMANTAP) is an internal quality assurance system developed at Universitas Prasetiya Mulya. In its development, SIMANTAP still requires the development of the degree audit module and the outcome-based education (OBE) curriculum module. The degree audit module is needed due to the requirement for validating student graduation for the Applied STEM faculty. Meanwhile, the OBE curriculum is essential for accreditation purposes for all Applied STEM programs before graduation. This research encompasses stages starting from discussions with the admin & program head, planning, system specification determination, system design, system development using the Django framework as the backend and the ReactJS framework as the frontend, and functional system testing. Through this research, it is expected that the system will facilitate the administrative tasks related to curriculum and graduation processes conducted in the Applied STEM faculty at Universitas Prasetiya Mulya.